2012
DOI: 10.5173/ceju.2012.03.art6
|View full text |Cite
|
Sign up to set email alerts
|

BPH Thulium laser enucleation of the prostate (TmLEP) vs. transurethral resection of the prostate (TURP): evaluation of early results

Abstract: IntroductionThe first decade of XXI century it is a time of the thulium laser implementation to a benign prostatic hyperplasia treatment.ObjectiveThe objective of this paper is a comparative assessment of early results thulium laser enucleation of the prostate (TmLEP) versus transurethral resection of the prostate (TURP) in 3-months observation.Materials and methodsPatients were randomized to BPH surgical treatment: research group (TmLEP – 54 men) or control group (TURP – 52 men). Between 02.2007-09.2009 non-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 13 publications
1
52
2
3
Order By: Relevance
“…As a result, only five studies provided surgical data for analysis. The latter studies include two prospective cohorts (level of evidence IIa) and three randomized controlled trials comparing ThuLEP with TURP or HoLEP (level of evidence 1b) [6][7][8][9][10]. The study of Shao et al [8] was in Chinese, and data were extracted by the English abstract and after personal communication with the authors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As a result, only five studies provided surgical data for analysis. The latter studies include two prospective cohorts (level of evidence IIa) and three randomized controlled trials comparing ThuLEP with TURP or HoLEP (level of evidence 1b) [6][7][8][9][10]. The study of Shao et al [8] was in Chinese, and data were extracted by the English abstract and after personal communication with the authors.…”
Section: Resultsmentioning
confidence: 99%
“…Iacono et al [6] enrolled patients with prostate volumes (PV) larger than 75 cc (median 108.08 ml), whereas Zhang et al [9] enrolled patients with PV < 80 ml (median 46.6 ml in the ThuLEP arm). In contrast, Świniarski et al [10] and Rausch et al [7] enrolled consecutive patients with PV of any size (28-126 and 17-180 ml accordingly) with a median of 62 and 85 ml for ThuLEP cases accordingly. The above heterogeneity should be taken into consideration when evaluating ThuLEP results given that prostatic volume is a well-established predictor of perioperative outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have shown that SOL is a safe and efficient treatment for patients with benign prostate hyperplasia after transurethral resection of the prostate (8,13). Reports also suggest that TURP is low risk, highly safe and associated with less complications when treating benign prostate hyperplasia (14,15). In this study, we investigated the efficacy of different dosages of SOL for patients with benign prostate hyperplasia during the perioperative period.…”
Section: Discussionmentioning
confidence: 99%